2013
DOI: 10.1111/tbed.12010
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Geometric Validation Approach to Assess the Basic Behaviour of Space- and Time- Distributed Models of Epidemic Spread - An Example Using the Ontario Rabies Model

Abstract: Dynamic mathematical modelling and stochastic simulation of disease-host systems for the purpose of epidemiological analysis offer great opportunities for testing hypotheses, especially when field experiments are impractical or when there is a need to evaluate multiple experimental scenarios. This, combined with the ever increasing computer power available to researchers, has contributed to the development of many mathematical models for epidemic simulations, such as the individual-based model (IBM). Neverthel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…; Rees ; Ludwig et al . ). Because sensitivity analysis indicated strong disease response to the disease transmission parameter and because this parameter was estimated by a model fitting process similar to Smith et al .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Rees ; Ludwig et al . ). Because sensitivity analysis indicated strong disease response to the disease transmission parameter and because this parameter was estimated by a model fitting process similar to Smith et al .…”
Section: Methodsmentioning
confidence: 97%
“…Values for population and disease dynamics input parameters (Table 1) were primarily drawn from empirical scientific studies for the mid-latitude eastern North American raccoon and rabies system, primarily from Ontario, Canada (Rees et al 2008). Validity and sensitivity analyses demonstrated that the model parameter set was parsimonious and that the model responded to input parameters as expected (Rees et al 2004;Rees 2007;Ludwig et al 2012). Because sensitivity analysis indicated strong disease response to the disease transmission parameter and because this parameter was estimated by a model fitting process similar to Smith et al (2002) rather than from direct empirical evidence, we conducted further experiment-specific sensitivity analyses described in the following statistical analysis section.…”
Section: Inputmentioning
confidence: 98%
“…Model processes were stochastically determined and operated at a weekly interval. Validity and sensitivity analyses demonstrated that the model parameter set simulated the expected raccoon demographics and RRV dynamics (Ludwig, Berthiaume, Richer, Tinline, & Bigras‐Poulin, ; Rees, ; Rees, Pond, Tinline, & Ball, ; Rees et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Validity and sensitivity analyses demonstrated that the model parameter set simulated the expected raccoon demographics and RRV dynamics (Ludwig, Berthiaume, Richer, Tinline, & Bigras-Poulin, 2012;Rees, 2007;Rees, Pond, Tinline, & Ball, 2004;Rees et al, 2013). We created two model landscapes.…”
Section: Simulation Landscapesmentioning
confidence: 99%